PENERAPAN PEMBELAAN TERPAKSA DALAM PERISTIWA PENCURIAN DENGAN KEKERASAN (Studi Kasus di Kepolisian Resor Metropolitan Bekasi Kota) - Putri, Intan Khaula; R, Mukhlis; Andrikasmi, Sukamariko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
One thing that can explain the power of the police in carrying out theirduties is the discretion or authority given by law to act in special situationsaccording to the judgment and conscience of the police themselves. Given thatthis authority is very broad, it requires requirements that must be possessed byofficers, especially in assessing a case, especially cases that threaten propertyand even the safety of one's life. Nevertheless, the authority to declare someoneguilty of committing a criminal offense is the panel of judges through a courtdecision. However, there are cases that researchers analyze where victims whomake defense efforts are forced to have a different final settlement from the lawenforcement process in previous similar cases.This type of research can be classified into empirical sociologicalresearch. With the research location located in Bekasi City, especially in thejurisdiction of the Bekasi City Metropolitan Police, while the population andsample are all parties related to the problem under study. This research uses datasources in the form of primary data and secondary data, and data collectiontechniques are carried out by interview.From the results of the problem research, there are 3 main things that canbe concluded. First, Noodweer is the authority of the judge who assesses, so thereis no rule that authorizes the police to stop the investigation or not continue acase due to applying the reasons for criminal erasure, Indonesian National Policeofficers in carrying out their duties and authorities can act according to their ownjudgment. However, the case of Muhammad Irfan Bahri proves the ability of lawenforcement officials to convince the public that these institutions can providemaximum protection and ensure the safety of victims. Third, the ideal idea of theinvestigator's action in applying the reason for criminal nullification according tothe concept of noodweer for the future is to limit discretion to prevent arbitraryactions with consideration of the principle of necessity, the principle ofstraightforwardness and integrity, the principle of benefits and objectives and theprinciple of balance.Keywords: Forced Defense, Investigator, Discretion.